Implementation of the integrated approach in different types of exposure scenarios. (October 2018) - Copplestone, D.; Hirth, G.; Johansen, M.; Lazo, E.; Takala, J.; Sakai, K.; Yankovich, T.
The International Commission on Radiological Protection (ICRP) recognises three types of exposure situations: planned, existing, and emergency. In all three situations, the release of radionuclides into the natural environment leads to exposures of non-human biota, as well as the potential for exposures of the public. This paper describes how the key principles of the ICRP system of radiological protection apply to non-human biota and members of the public in each of these exposure situations. Current work in this area within ICRP Task Group 105 is highlighted. For example, how simplified numeric criteria may be used in planned exposure situations that are protective of both the public and non-human biota. In emergency exposure situations, the initial response will always be focused on human protection; however, understanding the potential impacts of radionuclide releases on non-human biota will likely become important in terms of communication as governments and the public seek to understand the exposures that are occurring. For existing exposure situations, there is a need to better understand the potential impacts of radionuclides on animals and plants, especially when deciding on protective actions. Understanding the comparative impacts from radiological, non-radiological, and physical aspects is often important in managing the remediation of legacy sites. Task Group 105 is making use of case studies of how exposure situations have been managed in the past to provide additional guidance and advice for the protection of non-human biota.